The impact of women directorship on real estate companies: a case in Malaysia - Abdullah, Zaimah; Amran, Noor Afza; Ishak, Rokiah (Serials Publications, 2017)
Worldwide, real estate industry is prevalent with its unpleasant image of corruption, political intervention and bribery. Women directorship is portrayed as one of the possible solutions that may neutralize the attributes that have undermined the credibility of these companies. Thus, the main aim of this study is to understand the pattern of women directorship in Malaysian real estate companies and its relationship with companies’ performance and value. Employing a robust statistical technique, GLS regression estimation and by utilising panel data spans of four years from 2012 to 2015, this study finds that the presence of women director(s) on Malaysian real estate corporate board has no impact on companies’ performance as well as on its value creation.